18F-Choline Uptake in Acute Ischemic Stroke. (February 2017) - Delaunay, Kostas; Le Jeune, Florence; Garin, Etienne; Devillers, Anne; Palard-Novello, Xavier
Abstract : Abstract: A 75-year-old man with a history of prostate cancer was referred to our department to perform 18 F-choline (FCH) PET/CT. FCH PET/CT showed a markedly increased uptake in the right temporoparietal junction brain. Three weeks earlier, acute ischemic stroke was diagnosed in the right temporoparietal junction brain on diffusion-weighted sequence and thrombosis in a distal branch of the right middle cerebral artery on MR angiography. Choline precursors promote repair and growth of cell membranes in neurologic diseases, so FCH PET/CT uptake could be explained by repair processes during early outcome of acute ischemic stroke.